Chitosan from Crab Shell Waste for Soft Lithography of Bioplastic Diffraction Gratings - Gumayan, Efren G. (Archīum Ateneo, 2023)
Bioplastic diffraction gratings are fabricated from chitosan prepared from crab shells through a soft lithography replication process. Atomic force microscopy and diffraction experiments with the chitosan grating replicas indicate the successful copying of periodic nanoscale groove structures corresponding to densities of 600 and 1200 lines/mm. First-order efficiency of bioplastic gratings is comparable to the output of elastomeric grating replicas.